Correction: Helal et al. Improving Yield Components and Desirable Eating Quality of Two Wheat Genotypes Using Si and NanoSi Particles under Heat Stress. Plants 2022, 11, 1819 - Nesma M. Helal; Hemmat I. Khattab; Manal M. Emam; Gniewko Niedbała; Tomasz Wojciechowski; Inès Hammami; Nadiyah M. Alabdallah; Doaa Bahaa Eldin Darwish; Mohamed M. El-Mogy; Heba M. Hassan (Plants, 2023)
In the original publication [...]